109k views
2 votes
I need help on this please guys, thank you.

1. Add or subtract. Show your work for each problem by using boxes, circles, colored underlines, OR grouping
to identify the like terms before you simplify.
4 points each (1 point for correct answer, 3 points for showing ALL work.)
a. (−2x
^2 −4x+ 13)+ (12x
^2 + 2x −25) b. (7x
^2 + 4x − 26)− (−7x^
2 − 3x + 15)


2. Multiply. Show all your work including boxes, circles, colored underlines, distributing, OR grouping to identify
the like terms before you simplify.
6 points (1 point for correct answer, 5 points for showing ALL work)
(5x − 1)(6x
^2 + 3x + 7)
3. Find the roots. Show your work. List your steps correctly.
6 points (2 points for correct answer, 2 points for showing ALL work, 2 points for writing the steps of the
problem)

(n) = n
^2 − 6n − 16

I need help on this please guys, thank you. 1. Add or subtract. Show your work for-example-1

1 Answer

6 votes

Answer:

The solutions to your three problem question are:

1.

a. 10x^2 −2x -12

b. 14x^2 + 7x -41

2. 30x^3 + 9x^2 + 32x - 7

3.

n1 = 8

n2 = -2

Explanation:

1. First problem

We need to Add or subtract the expressions to find the equivalent terms

a) (−2x^2 −4x + 13)+ (12x^2 + 2x −25)

We add together the terms with the same exponent

= (−2x^2 + 12x^2 ) + (−4x + 2x) + (13 - 25)

= (10x^2 ) + (−2x) + (-12)

= 10x^2 −2x -12

b) (7x^2 + 4x − 26)− (−7x^2 − 3x + 15)

= (7x^2 + 4x − 26) + (7x^2 + 3x - 15)

We add together the terms with the same exponent

= (7x^2 + 7x^2 ) + (4x + 3x) + (- 26 -15)

= (14x^2 ) + (7x) + (-41)

= 14x^2 + 7x -41

2. Second problem

(5x − 1)(6x^2 + 3x + 7)

We need to multiply to find the equivalent expression\

(5x − 1)(6x^2 + 3x + 7) = (5x)*(6x^2 + 3x + 7) + (-1)*(6x^2 + 3x + 7)

= [(5x)*(6x^2 + 3x + 7)] + [-6x^2 - 3x - 7]

= [(5x*6x^2) + (5x*3x) + (5x*7)] + [-6x^2 - 3x - 7]

= [(30x^3) + (15x^2) + (35x)] + [-6x^2 - 3x - 7]

We add together the remaining terms

= [(30x^3) + (15x^2 - 6x^2) + (35x - 3x) - 7]

= (30x^3) + (9x^2) + (32x) - 7

= 30x^3 + 9x^2 + 32x - 7

3. Third problem

f(n) = n^2 − 6n − 16

We need to find the roots for the polynomial f(n)

That is, the values of n for which f(n) = 0

We can find an analysis of the function in the images below.

Lets use the quadratic formula

Let y = ax2 + bx + c

a = 1

b = -6

c = -16

x = -b/(2*a) ± sqrt(b^2 -4ac)/(2*a)

x = 3 ± 10/2 = 3 ± 5

roots

n1 = 8

n2 = -2

I need help on this please guys, thank you. 1. Add or subtract. Show your work for-example-1
I need help on this please guys, thank you. 1. Add or subtract. Show your work for-example-2
User Yahia Zakaria
by
5.9k points